Judiciary Saga in Poland: an Affair Torn Between European Standards and ECtHR Criteria - Mastracci, Matteo (Polish Review of International and European Law, 2020)
Judicial independence is a cornerstone of contemporary constitutional systems within European legal orders that Poland, among many other European States, codified the principle at a constitutional level through Article 173 of the Constitution of the Republic of Poland. Nonetheless, the concrete implementation of the theoretical framework remains a bone of contention between the national States and the main international actors. The latter faction, based on the acknowledgement that no single political model could ideally comply with the principle of the separation of powers and secure complete independence of the judiciary, has developed an impressive number of legal tools that are part of a more diffuse European trend of interpretation, which should be labelled as European standard or European corpus aiming at preserving the judiciary order from outward interferences by the legislative and executive powers. In Poland, after the extensive victory earned by the Law and Justice (PIS) party in the Parliamentary election of 2015, the executive branch propelled a series of interlock reforms with the aim of reshuffling the whole judicial asset of the country. In the first place, the way forward was marked by a compound diatribe concerning the Constitutional Tribunal, and the essence of the dispute concerned the mandate’s legitimacy of three sitting judges after the Court’s reinterpretation of the K 34/15 ruling that ended up on 2.12.2015 with the election of five new judges appointed ex novo by the ruling party. Afterwards, the attention shifted towards the rethinking of the National Council of Judiciary (KRS), a mixed judicial body guardian of the independence of the judiciary, asserting, firstly, the unconstitutionality of its statute and, subsequently, planning a new method of appointment for the judicial members previously elected by the judiciary itself. Ultimately, as a closing step, the spotlight turned in the direction of the Supreme Courts judges, where the most spectacular sweep was the provision aimed at lowering the retirement age for the sitting judges on a scheme similar to the proposal made by the Hungarian government in 2011, where voices were raised, respectively, by the Hungarian Constitutional Court, the European Court of Justice and the European Court of Human Rights, and where, regretfully, the judicial independence standard played a minor role in the Courts’ reasoning. This concluding phase convinced the Commission to launch an expedited procedure against Poland before the Court of Justice, thus forcing the Polish government to retracts previous law through the adoption of a repealing law on 17.12.2018; in any event, as predicted earlier by the Opinion delivered by the AG Tanchev in Case C-619/18, the ECJ epilogue released on 24.6.2019, dissimilar to the one reached in the Hungarian case, was the heaviest ‘contrariness to EU law’.